Organizational and social barriers for the practice of physical activity in the oldness - J. Martínez del Castillo; J.E. Jiménez-Beatty; A. Campos; D. Del Hierro; Mª. Martín; Mª.D. González (Asociación Española de Ciencias del Deporte, 2010)
The article approaches the social barriers and the organizational barriers that seem to impede the accomplishment of physical activity in the oldness. The methodology has consisted of the accomplishment of interviews face to face to a sample, selected by means of a sampling multistage of the sixty five-year-old Spanish population fulfilled or more. The participants present the following characteristics: 53,1 % is women and 46,9 % males; 54,7 % had between 65 and 74 years and 45,3 % was overcoming 75 years. The instrument used in the investigation has consisted of a questionnaire with closed questions and a scale of barrier perception for the practice of physical weekly activity. The results show the existence of 12,8 % of major persons that they want to practise but not to be able to do it for any barriers. The principal organizational barriers perceived are in diminishing order: inconvenient schedule; do not be where to do it; the price is high; the site is far. The principal barriers related to the social environments on behalf of these persons are: not to have time and his relatives or friends would get upset. Key Words:physical activity, oldness, organizational barriers, social barriers.